PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Samuel Robert; Tina Melinda (Media Mahardhika, 2018)
The ministry of trade in the last few years noted that the export of rattan, wood, and comparable products have always increased. This indicates that the rattan and wood industry is quite promising. Mas Mulia is a family-based company engaged in the rattan and wood processing since 1999 with the production of semi-finished or furniture form product. Due to that positive trend makes the number of competitors in this industry raise. Therefore the company needs to improve its performance to be able to compete globally, starting from the performance of its employees. Researcher sees a decrease in motivation that showed in the employee attendance, this will be very influential to the employee performance because the workload from the employees who are not present can not be left alone and must be covered by another employee which will ultimately reduce the performance of the other employees. Another thing that researcher sees is the high number of employee that quit which never happened to the previous leader. This will reduce employee performance because the new guy will take time to adapt and understand how company works in advance which will take longer to adapt. Therefore this research will aimed to determine the influence of motivation and leadership on employee performance. This research used quantitative method and multiple regression analysis model involving 30 respondents. Data is processed using Statistical Product and Service Solutions (SPSS) program version 22. The result of this research shows that motivation and leadership have an impact towards employee performance. Both motivation and leadership have an impact for 64% and 36% influenced by the factors that didn’t discussed in this research.